Micro- and nanotechnology for cell biophysics - Galajda, Péter; Kelemen, Lóránd; Végh, Gergely A. (Acta Biologica Szegediensis, 2015)
Procedures and methodologies used in cell biophysics have been improved tremendously with the revolutionary advances witnessed in the micro- and nanotechnology in the last two decades. With the advent of microfluidics it became possible to reduce laboratory-sized equipment to the scale of a microscope slide allowing massive parallelization of measurements with extremely low sample volume at the cellular level. Optical micromanipulation has been used to measure forces or distances or to alter the behavior of biological systems from the level of DNA to organelles or entire organisms. Among the main advantages is its non-invasiveness, giving researchers an invisible micro-hand to “touch” or “feel” the system under study, its freely and very often quickly adjustable experimental parameters such as wavelength, optical power or intensity distribution. Atomic force microscopy (AFM) opened avenues for in vitro biological applications concerning with single molecule imaging, cellular mechanics or morphology. As it can operate in liquid environment and at human body temperature, it became the most reliable and accurate nanoforce-tool in the research of cell biophysics. In this paper we review how the above three techniques help increase our knowledge in biophysics at the cellular level.